Overcrowded as normal: governance, adaptation, and chronic capacity stress in the England and Wales prison system, 1979 to 2009 - Bastow, Simon (2012)
Why do public policy systems sustain chronic conditions despite general consensus that these conditions are detrimental to overall performance? The answer is because they are, in one way or another, sustainable. Systems find ways of sustaining manageable and acceptable equilibrium between demand for their services and their supply. Yet in doing so, they develop ways of coping with and normalizing situations of chronicness. This research is about chronic capacity stress (CCS) in a large and complex public policy system. CCS may be caused by excessive demand for services. It may also be caused by inadequate supply. Either way, it is a property of sustainable equilibrium between the two, and therefore must be understood in these dynamic terms rather than as just the product of one or the other. I examine overcrowding in the England and Wales prison system as an archetypal case of CCS. It starts with the assumption that the prison system should in theory be set up to deal with the demands made upon it. In doing so, it examines the way in which the system itself has coped with, normalized, and sustained crowding over the years. I have conducted in-depth interviewing with former ministers, top officials, governors, and other key actors, as well as extensive quantitative analysis covering three decades. I develop four inter-related themes as a part of a ‘problematique’ which explains why CCS is sustained: ambivalence towards rehabilitation, coping and crisis culture, benign resistance, and obsolescence and redundancy. Constrained autonomy of actors and their adaptive behaviours are key to understanding how the system sustains CCS, and how it is able to function despite CCS. Ultimately, I show how three groups of public policy theory – public choice, cultural theory, and governance - are vital aspects of an overall explanation, but that independently they are insufficient to explain why chronicness sustains, and therefore must be integrated into a more holistic, governance-style explanation. CCS can be seen as a function of governance dysfunction